LA NOCIÓN DE DISUASIÓN INTEGRADA DE ESTADOS UNIDOS: ¿REALIDAD O FANTASÍA PARA LATINOAMÉRICA? (Glocalism: Journal of Culture, Politics and Innovation, 2025)
This article delves into the “Integrated Deterrence of the United States”, unveiled at the XV Conference of Ministers of Defense of the Americas (CMDA) in 2022, which sparked numerous international debates and led to varied interpretations regarding its implications. This study aims to examine this discourse by highlighting Latin America’s distinct characteristics and conducting an in-depth analysis of security and defense challenges projected over the forthcoming decade. A range of bibliographic sources were reviewed to understand the concepts and implications and to envision the strategic concept’s applicability. The U.S. proposal was juxtaposed with contemporary risks, threats, and factors that enhance risk, which diverge from traditional elements. Consequently, it was determined that the U.S. strategy does not allow for a comprehensive application of the strategic model in the region, given the distinct characteristics present in each territory.
Keywords: American studies; integrated deterrence; international relations; national defense strategy; security studies